Motives Of Internal Revolutions Phenomenon On Arab Political Regimes (Global Journal of Human-Social Science, 2012)
Internal Revolutions Phenomenon on the Arab Political Regimes is considered a compound phenomenon that was aroused from a combined number of elements and their combination in a way that we can not assume that the cause of this phenomenon returns to one reason or an element without the other reasons or elements We can not understand this phenomenon unless within the factors network and reasons that led to its appearance In order to achieve the purpose of this study a random sample of 280 individuals was selected who represent different segments from the intellectuals and politicians those who are active in economic media religious and social in addition to the other interested people in the issue of internal revolutions from various Arab nationalities Where as a questionnaire which consisted of 55 questions has been distributed on five main themes equally it was discovered that the underlying political economic media religious and social reasons were the most important reasons that led to the internal revolutions where all the reasons got a positive arithmetic means It turns out that the economic factor was one of the strongest reasons that led to the emergence of revolutions in the Arab Countries The study also revealed that there are differences due to the impact of gender in the study sample individuals In addition no differences were found due to the impact of marital status on the opinions of the study sample individuals As for the correlation among all the reasons leading to the internal revolutions it has been shown that there is no correlation between the political reasons and religious reasons of the internal revolutions
Keywords: Internal Revolutions; Arab; Political Regimes